Laparoscopic Toupet Fundoplication using an Air Seal Intelligent Flow System and Anchor Port in a 1.8‐kg infant: A Technical Report. Issue 3 (25th August 2015) - Miyano, Go; Morita, Keiichi; Kaneshiro, Masakatsu; Miyake, Hiromu; Nouso, Hiroshi; Yamoto, Masaya; Koyama, Mariko; Nakano, Reiji; Tanaka, Yasuhiko; Fukumoto, Koji; Urushihara, Naoto
Abstract Introduction We report a case of a 1.8‐kg infant who had laparoscopic Toupet fundoplication (LTF) using the AirSeal Intelligent Flow System and Anchor Port (AP). Materials and Surgical Technique Our case had severe gastroesophageal reflux in association with genetic and cardiac anomalies. Despite the patient being continuously fed, persistent vomiting caused failure to thrive, and LTF was performed at 4 months of age when he weighed 1.8 kg. The AirSeal Intelligent Flow System is a novel laparoscopic CO2 insufflation system that improves the visual field by constantly evacuating smoke and providing a more stable pneumoperitoneum. The AP is a recently developed, stretchable, elastomeric, low‐profile cannula. Three 5‐mm AP were inserted: one subumbilically for the scope and one in both the right and left upper abdomen for the surgeon. A 5‐mm AirSeal trocar was inserted in the left lower abdomen for the assistant. The gastrosplenic ligament was dissected free, and the intra‐abdominal esophagus was prepared. A posterior hiatoplasty was performed, followed by the 270° fundoplication. During the fundoplication, the esophagus was fixed to the crus and then the right and left wraps were fixed to the esophagus. Pneumoperitoneum was maintained stably throughout the LTF procedure, with optimal operative field. Total operating time for LTF was 90 min. Body temperature dropped from 37.4°C to 35.7°C during pneumoperitoneum but resolved once pneumoperitoneum was ceased. Postoperative progress was uneventful, and an upper gastrointestinal study on postoperative day 2 showed no residual gastroesophageal reflux. Discussion We believe the AirSeal Intelligent Flow System and AP contributed to the successful completion of LTF in a 1.8‐kg infant.